Argument-based approach to computer system safety engineering. (1st January 2012) - Yuan, Tangming; Kelly, Tim
Safety case development is not a post-development activity, rather it should occur throughout the system development lifecycle. The key components in a safety case are safety arguments. Too often, safety arguments are constructed without proper reasoning. Inappropriate reasoning in safety arguments could undermine a system's safety claims, which in turn contributes to safety-related failures of the system. To address this, we argue that informal logic argument schemes have important roles to play in safety arguments construction and review process. Ten commonly used reasoning schemes in computer system safety domain are proposed against the safety engineering literature. The role of informal logic dialogue games in computer system safety arguments reviewing is also discussed and a dialectical model for safety argument review is proposed. It is anticipated that this work will contribute toward the development of computer system safety arguments, and help to move forward the interplay between research in informal logic and research in computer system safety engineering.